Overcoming Instructional Obstacles: The Implementation of Diverse EFL Teaching Strategies in Higher Education - Febriyanti Hulopi; Anas Amu (PT MEDIA JURNAL DAN PENDIDIKAN, 2025)
Teaching English as a Foreign Language (EFL) at the university level requires educators to dynamically implement various teaching strategies to meet diverse student needs. This research aimed to discover the specific strategies lecturers use in teaching English and explore the practical obstacles they face during implementation at Universitas Pohuwato. Employing a qualitative descriptive research method, data were systematically gathered through in-depth audio-recorded interviews with four English lecturers. The processed results reveal that lecturers utilize a multifaceted approach: interactive strategies, visualization, question-and-answer sessions, cooperative student-centered models, role-play, and drilling. Despite these robust strategies, their effectiveness is heavily moderated by several pedagogical and systemic obstacles. These include severe classroom management issues due to large student capacities, significant lack of student vocabulary mastery, poor interpersonal communication among learners, and the absence of adequate technological infrastructure, such as LCD projectors. In conclusion, while lecturers demonstrate pedagogical adaptability, university management must provide better infrastructure and balanced class sizes to fully optimize these EFL teaching strategies